Abnormally Shallow Boundary Layer Associated With Severe Air Pollution During the COVID‐19 Lockdown in China. Issue 20 (19th October 2020) - Su, Tianning; Li, Zhanqing; Zheng, Youtong; Luan, Qingzu; Guo, Jianping
Abstract: After the 2020 Lunar New Year, the Chinese government implemented a strict nationwide lockdown to inhibit the spread of the Coronavirus Disease 2019 (COVID‐19). Despite the abrupt decreases in gaseous emissions caused by record‐low anthropogenic activities, severe haze pollution occurred in northern China during the COVID lockdown. This paradox has attracted the attention of both the public and the scientific community. By analyzing comprehensive measurements of air pollutants, planetary boundary layer (PBL) height, and surface meteorology, we show that the severe air pollution episode over northern China coincided with the abnormally low PBL height, which had reduced by 45%, triggering strong aerosol‐PBL interactions. After dynamical processes initiated the temperature inversion, the Beijing metropolitan area experienced a period with continuously shallow PBLs during the lockdown. This unprecedented event provided an experiment showcasing the role of meteorology, in particular aerosol‐PBL interactions in affecting air quality. Key Points: Based on nationwide observations, variations in air pollution and meteorology are discussed during the COVID lockdown The severe air pollution during the lockdown coincided with abnormally shallow PBL triggering strong aerosol‐PBL interactions Beijing experienced a period with continuously shallow PBLs initiated by dynamical processes, which warrant the formation of haze event